1985
DOI: 10.1007/bf01849793
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting injectable microsphere formulation for the parenteral administration of levonorgestrel

Abstract: The pharmacokinetic and pharmacodynamic effects of a long-acting formulation of levonorgestrel microencapsulated in a biodegradable polymer poly(DL-lactide-CO-glycolide) was tested in baboons. The polymer microspheres provided continuous release of levonorgestrel for up to 6 months following a single intramuscular injection. The treatment inhibits ovarian function for 3-6 months, depending on the dose. The duration and pattern of levonorgestrel release varies according to the quality and size of the microspher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…11,12 Therefore, a sustained release system is needed to prolong the action of local anesthetic as well as to avoid the inconvenience of patients and to maintain constant therapeutic levels. 13 The development of long-acting local anesthetics is also needed for postoperative analgesia and control of chronic pain of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Therefore, a sustained release system is needed to prolong the action of local anesthetic as well as to avoid the inconvenience of patients and to maintain constant therapeutic levels. 13 The development of long-acting local anesthetics is also needed for postoperative analgesia and control of chronic pain of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contraceptive research, PLG, PLA and PLGA have shown promise for the controlled release of LNG both in vitro and in vivo [26][27][28][29][30][31]. Additionally, PLGA microspheres have been evaluated in vivo for delivery of Nestorone, a potent contraceptive progestin being developed by the Population Council in a variety of formulations.…”
Section: Past Researchmentioning
confidence: 98%
“…Drug microcrystal suspensions, drug-loaded microsphere suspensions, and in situ forming depot systems are among the most common injectable dosage forms to achieve sustained release of APIs (2,(17)(18)(19). Each dosage form has its own advantages and disadvantages which are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In situ forming depots have advantages of simplicity of manufacture, reconstitution un-necessary, and versatility. However, they have disadvantages of using organic solvents as vehicles, forming depots in vivo with non-precise shapes and sizes, and requiring drugs with broad therapeutic windows (19,30). All the above three dosage forms have been used to develop long-acting injectable contraceptives.…”
Section: Introductionmentioning
confidence: 99%